2007
DOI: 10.1038/sj.bmt.1705922
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose MTX for the treatment of acute and chronic graft-versus-host disease in children

Abstract: We report the results of a retrospective analysis in 27 pediatric patients who received low-dose MTX as the second-line treatment for steroid-refractory or -dependent acute and chronic GVHD. Between July 2000 and May 2006, 10 patients with aGVHD and 17 with cGVHD were treated with MTX at a dose of 3-10 mg/m 2 weekly. Seven of ten patients (70%) with aGVHD responded well to MTX, thus resulting in the achievement of either a complete response (CR) or a partial response (PR). The dose of prednisone could be reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
1
29
1
1
Order By: Relevance
“…In a study of 86 patients with cGVHD, a marked benefit in cutaneous disease was observed with low-dose methotrexate as the first-line treatment in combination with other immunosuppressants [150]. Other smaller studies have also shown efficacious results as well [151,152].…”
Section: Methotrexatementioning
confidence: 93%
“…In a study of 86 patients with cGVHD, a marked benefit in cutaneous disease was observed with low-dose methotrexate as the first-line treatment in combination with other immunosuppressants [150]. Other smaller studies have also shown efficacious results as well [151,152].…”
Section: Methotrexatementioning
confidence: 93%
“…While the degree of improvement for PR was not well defined, the authors reported an objective response in 10 (4 CR, 6 PR) of 17 patients, with all but one able to taper prednisone <0AE4 mg/kg/d. Interestingly, 6 of 11 patients with liver involvement had improvement (Inagaki et al, 2008). Infectious toxicity was minimal, making this common agent worthy of further prospective study, especially in patients that are already heavily immunosuppressed.…”
Section: Methotrexatementioning
confidence: 99%
“…Low-dose methotrexate is commonly used for arthritis (van Ede et al, 1998). Inagaki et al (2008) treated 17 paediatric patients with steroid-refractory or dependent chronic GVHD with low dose methotrexate (5-10 mg/m 2 ). Patients received this agent for a median of 18 months; therefore, it appeared to be well-tolerated.…”
Section: Methotrexatementioning
confidence: 99%
“…They suggested the effectiveness of rituximab therapy for selected patients with steroid-refractory chronic GVHD that is not advanced. Inagaki et al [131] demonstrated that administration of MTX at a dose of 3-10 mg/m 2 weekly had allowed steroid treatment to be reduced or discontinued in 15 (88 %) of 17 pediatric patients with steroid-refractory or steroiddependent chronic GVHD. Hidaka et al [151] reported the efficacy of bezafibrate for liver chronic GVHD with a poor response to ursodeoxycholic acid.…”
Section: Initial Therapy Of Chronic Gvhdmentioning
confidence: 99%
“…Iida et al conducted a nationwide survey to analyze the outcomes of patients who had received MMF as GVHD therapy after related [52] or unrelated [53] donor transplantation. Inagaki et al [131,132] suggested the efficacy of low-dose MTX at a dose of 10 mg/m 2 weekly for pediatric patients in two retrospective studies. They concluded that low-dose MTX therapy has a low risk of opportunistic infection, is low toxicity, is easy to administer, and is inexpensive.…”
Section: Second-line Therapy Of Acute Gvhdmentioning
confidence: 99%